Contemporary French Administrative Law - Bell, John (Social Sciences, 2022)
Written from a comparative perspective, this book offers an authoritative English-language introduction to the key features of French administrative law and institutions. Using a systematic approach and with a variety of illustrative case study, this is a valuable resource for any student or researcher with an interest in French law.